2009
DOI: 10.1016/j.carres.2009.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics studies of the conformation of sorbitol

Abstract: Molecular dynamics simulations of a 3 m aqueous solution of D-sorbitol (also called D-glucitol) have been performed at 300 K, as well as at two elevated temperatures to promote conformational transitions. In principle, sorbitol is more flexible than glucose since it does not contain a constraining ring. However, a conformational analysis revealed that the sorbitol chain remains extended in solution, in contrast to the bent conformation found experimentally in the crystalline form. While there are 243 staggered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…3(a)), in agreement with a previous report. 52 It is significant that the onset of the localised sub-regions occurs near 260 K, corresponding to the T ga of sorbitol, while significant localisation occurs near 180 K, corresponding to the T gb of sorbitol. An analysis of the time-evolution of dihedral angles in glassy sorbitol helps to uncover the changes in atomic dynamics that occur as a function of temperature in such disordered molecular solids.…”
Section: Ab Initio Molecular Dynamics (Aimd)mentioning
confidence: 99%
“…3(a)), in agreement with a previous report. 52 It is significant that the onset of the localised sub-regions occurs near 260 K, corresponding to the T ga of sorbitol, while significant localisation occurs near 180 K, corresponding to the T gb of sorbitol. An analysis of the time-evolution of dihedral angles in glassy sorbitol helps to uncover the changes in atomic dynamics that occur as a function of temperature in such disordered molecular solids.…”
Section: Ab Initio Molecular Dynamics (Aimd)mentioning
confidence: 99%
“…, refs 27,28,29,30,31,32,33,34,35, 36,37,38,39,40). MD with alkyl-glycosides (such as alkyl- β - O -glucoside (C 8 Glc 1 ) or alkyl-β- O -galactoside (C 8 Gal)) have been also performed in the past, involving bilayers,41, 42, 43 micelles 44,45, 46, 47 or interacting with a plant protein 48.…”
Section: Introductionmentioning
confidence: 99%
“…A small difference was seen, however, between the average sorbitol conformation in this study and that reported previously. 22,23 This difference arises only in the terminal torsional angle, and may arise from intermolecular interactions between sugar solute molecules due to the large difference in concentrations between the two studies (infinite dilution in the previous work and 1 molal here), and perhaps the water model used.…”
Section: Resultsmentioning
confidence: 95%
“…9 The water molecules were modeled using the TIP4P model. 26 Therefore, with respect to previous simulations on sorbitol reported in the literature, 22,23 the present study introduces both a new force field and a new water model. The simulation was implemented following the general procedures previously used to simulate pure aqueous solutions of caffeine 9 and of caffeine in glucose and sucrose solution.…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation